Organic Photovoltaic Cells based on Graphene Interfacial Anode Electrodes. (2016) - Pechlivani, E.M.; Papas, D.; Zachariadis, A.; Laskarakis, A.; Logothetidis, S.
Abstract: In this work we present the methodology for application of Chemical vapour Deposition (CVD) grown graphene layer as a hole transport interfacial layer in organic photovoltaic cells (OPVs) on glass/ITO substrates. The graphene nanolayers were synthesized by CVD on 6 inch Cu coated Si wafer. The quality of the grown graphene and the low amount of structural defects were investigated by Raman Spectroscopy mapping along the radial direction of the Cu wafer, whereas the stacking order of graphene layers onto the target substrates and their surface nanomorphology has been investigated by Atomic Force Microscopy (AFM). The Thermal Release Tape (TRT) method has been implemented for the transfer of the graphene nanolayers from the Cu wafer catalyst on the OPV structure. In order to ensure the uniform covering of graphene in the OPV structure from water based organic donor, a thin polymeric buffer layer has been deposited between their interfaces. As it has been found, the implementation of a graphene monolayer in the OPV device structure promotes the increase of its efficiency due to graphene's hole transport mobility.